Preventing and Combatting Domestic Violence: Incrementalism and Interest Groups in Ukrainian Public Policy - Puhach, Veronika; Demianchuk, Oleksandr (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2023)
Statistical data indicates that domestic violence in present-day Ukraine is a particularly acute phenomenon. Urgent policy responses are therefore required on the part of state authorities in order to prevent and combat the problem. Moreover, Ukraine must improve its legislation in this regard in order to meet international obligations and achieve legislative approximation with the European Union (EU) in connection with EU membership. But for eleven years until June 2022, Ukraine underwent significant struggles in this sphere and was unable to ratify the Council of Europe Convention on Preventing and Combating Violence against Women and Domestic Violence (the Istanbul Convention). This article turns to incrementalism and interest-group analysis for an exploration of both the challenges in ratifying the Istanbul Convention in Ukraine and the policy-making process that was adopted on account of those challenges. Using the case of domestic-violence legislation in Ukraine and the issue of the ratification of the Istanbul Convention, the authors contend that incrementalism remains a viable policy-making practice, as it considers a variety of stakeholders (including interest groups) and promotes progress by fostering common-ground approaches and gradual improvements. Ukraine’s trajectory ultimately shifted when the Istanbul Convention was ratified in 2022. Diverging from incrementalism in such a way, though, risks reversing crucial changes because the local opposition of interest groups in relation to a major decision remains unresolved. This article, first, reviews Ukraine’s policy path and show that it was incremental prior to 2022. Then, it looks at interest groups and examines their arguments for and against ratification of the Istanbul Convention. Afterward, the authors address the Europeanization of Ukraine and its impact on the adoption of legislation related to domestic violence. Finally, the article discusses how ratification became possible in 2022 and how EU conditionality both contributed to realizing that goal and created potential risks for the future.